Correção de erros em língua inglesa: do colaborativo ao individual - Côrtes, Letícia Martins (2013)
This study aims at investigating how the ways the students from the Ensino Fundamental review their text productions, when engaged in collaborative tasks, can influence the individual text revision in the English language. Our goal was to understand the revision strategies used by the learners during the collaborative task, analyze the text changes after the peer interactions considering affective factors, as well as examine the students’ perceptions about the collaborative and individual revision activities. Six students from the ninth year of the Ensino Fundamental of a public state school participated in this study case from August to December 2012. In order to collect the data, we made use of qualitative research principles and, at some moments, quantitative resources. For a better understanding of the learning, interaction and collaboration process, this study is based on the sociocultural theory, on theories about collaborative learning and on the affective factors in correction. The results show that the collaborative revision does not only promote a student’s text production improvement, through the positive atmosphere in which it is possible to learn from and teach his/her peer, but also the gradual development of the perception of the possibility of selfcorrection. The individual and collaborative reviews fostered a growing improvement in the level of preoccupation with lexical items, in terms of grammar, text organization and semantic content. Furthermore, these students have changed their awareness about the English language and the rewriting approach by understanding the necessity of revising and the importance of collaboration in the learning process.